Risk Factors for Antisocial Behavior in Low- and Middle-Income Countries: a Systematic Review of Longitudinal Studies - Murray, Joseph (Crime and justice, 2018)
Violent crime is a major cause of social instability, injury, and death in low- and middle-income countries. Longitudinal studies in high-income countries have provided important evidence on developmental precursors of violence and other antisocial behaviors. However, there may be unique influences or different risk factor effects in other social settings. Extensive searches in seven languages and screening of over 60,000 references identified 39 longitudinal studies of antisocial behavior in low- and middle-income countries. Many risk factors have roughly the same average effects as when studied in high-income countries. Stability of aggression over a 3-year period is almost identical across low- and middle-income countries and high-income countries. Dimensions of comorbid psychopathology such as low self-control, hyperactivity, and sensation seeking are associated with antisocial behavior in low- and middle-income countries, but some early physical health factors have consistently weak or null effects.